The Restoration of Alpha Generation Social Communication Post-Covid-19 Pandemic in TPQ (Taman Pendidikan Qur’an) Mujahidin Mojokerto - Fahmi, Lukman; Nuryana, Amiatun; Laila, Faizah Noer (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2024)
The social communication of the alpha generation in the current era, which is familiar with the digital environment due to the covid-19 pandemic, is a quite unique conversation to study because they spend more time with their gadgets than socialize with the people around them. As a result, this study aims to investigate how alpha generation social communication forms and the factors that cause them using the analysis of Brown et al’s. (1987) theory and Culpeper’s (2011) theory, and then this study aims to restore alpha generation social communication using behavior modification by using reward and punishment and economy token techniques. The descriptive qualitative method was used in this study. This study's findings include the discovered social communication forms in the politeness and impoliteness categories. Contributing factors include both parents' upbringing, friends from one's surroundings, social media, oneself, and others. And the end result of using behavior modification produces a genuine before-and-after behavior, such as providing a developmental impact on positive behavior and eliminating negative behavior.